APLICATION OF CHITOSAN FOR WATER QUALITY AND MACROBENTHIC FAUNA REHABILITATION IN VANNAMEI SHRIMPS (LITOPENAEUS VANNAMEI) PONDS, NORTH COAST OF SEMARANG, CENTRAL JAVA - INDONESIA - R. Ruswahyuni; Agus Hartoko; Siti Rudiyanti (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Chitosan was widely known as natural food preservative such as noodle, meat ball, soy-tofu, wide variety offresh vegetables, fruits, meat and fish products, etc. Chitosan is a non-toxic substances, has no side effect ashuman food and was made from the shell of shrimps (Penaeidae), or swimming crabs (Portunus pelagicus).Chitosan is primarily a polysacharids, with β-1,4-2 amino-2-deoxy- β- D-glucopyranose. The biopolymerhas various noble functional characters such as anti-moth, anti-bacterial, coagulating agent for suspension,or heavy metals. This substance had been examined in the Lab of Natural Product, Diponegoro Universityand give a significant effect as bacteriostatic and bactericides for pathogenic bacteria such as Salmonela.sp;Pseudomonas, E.coli, B.subtilis, S.aureus, P.aeruginosa. In the study, liquid chitosan (200 ppm) was used asanti- harmful/ pathogenic bacteria in the brackish water pond so that can eliminate and control the bacterialor virus outbreak which so far is the main problems in the fish and shrimp culture activities. The use ofchitosan in the brackish water ponds was carried out at a semi-traditional ponds at Mangkang Kulon northSemarang coastal area. The experiment had significantly decrease the suspended solid or increase watertransparency, and the organic content ( by 5 %) of the bottom susbtrate. Increase the abundance ofimportant macro-benthic organism such as Polychaeta (7-fold) as important natural feed for the cultured fishand shrimp as well as increase the diversity index of total macro-benthic organism. Decrease the growth ofdisease vector benthic organism such as Cherithidae (Gastropods) by 24.5% . With the application ofchitosan had significantly prevent the outbreak of fish and shrimp disease and increase up to 80 % thesurvival rate of Vanamae, as well as tiger shrimp Penaeus monodon, and polkadot grouper (Cromileptes,sp)in another field application.